Chlamydial Infection Prevalence in Human Immunodeficiency Virus Patients - Teja, Feilicia Henrica; Rowawi, Rasmia Rowawi; Soedarwoto, Asmaja; Puspitosari, Diah; Rasianti, Rini; Rahmatdinata, Rahmatdinata; Djadjakusumah, Tony (International Journal of Integrated Health Sciences, 2013)
Objective: To determine the prevalence of chlamydial infection in male urethra and female cervix of HIV-positive patients based on PCR assay in Teratai Clinic, Dr. Hasan Sadikin General Hospital Bandung. Methods: A cross sectional observational study with consecutive sampling method, which was conducted in Teratai Clinic during the month of July 2012. All participants underwent history taking, physical examination, and PCR assay for C. trachomatis. Swab samples were obtained from male urethra and female endocervix. Results: Eighty one HIV-positive patients, consisted of 48 males and 33 females were included in this study. The PCR examination for C. trachomatis was positive in 14 of 81 subjects (17.3%), with 10 (20.8%) urethral chlamydial infection in 48 males and four (12.1%) cervical chlamydial infection in 33 females. Conclusions: The study concluded that the prevalence of chlamydial infection in male urethra and female cervix of HIV-positive patients were 20.8% and 12.1%, respectively. Identifying chlamydial infection based on PCR testing should be considered for routine screening test in HIV-positive patients.    Keywords: Chlamydia trachomatis, HIV, prevalence, PCR DOI: 10.15850/ijihs.v1n1.107